2004
DOI: 10.1055/s-2004-834932
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Asymmetric Hydrosilylation of Ketones, Imines and Electrophilic Double Bonds

Abstract: This literature review focuses on the recent advances in the asymmetric hydrosilylation of ketones and imines. New catalyst systems based on various transition metals, such as rhodium, titanium, zinc, copper and tin, combined with classical or new ligand structures, are presented. These systems lead to very effective and selective protocols for the reduction of prochiral ketones, imines and electrophilic double bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
86
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(87 citation statements)
references
References 66 publications
(71 reference statements)
0
86
0
1
Order By: Relevance
“…[5] Notably, Buchwald et al reported the use of ansa-titanocene EBTHI with tetrahydroindenyl substituents as ligands for titanium, giving the products of hydrosilylation of ketones with up to 99% ee. [23] Zinc complexes of chiral secondary amines were introduced by Mimoun as chiral catalysts for the enantioselective hydrosilylation of ketones, with enantioselectivities up to 88% ee.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Notably, Buchwald et al reported the use of ansa-titanocene EBTHI with tetrahydroindenyl substituents as ligands for titanium, giving the products of hydrosilylation of ketones with up to 99% ee. [23] Zinc complexes of chiral secondary amines were introduced by Mimoun as chiral catalysts for the enantioselective hydrosilylation of ketones, with enantioselectivities up to 88% ee.…”
Section: Introductionmentioning
confidence: 99%
“…[1] In the case of ketones and imines, it also serves as a convenient reduction method in that it provides protected alcohols and amines in one step. [2] Whereas diverse procedures have been developed for the hydrosilylation of C = X (X = C, N, O), [1] P = O, [3] S = O, [4] and CC bonds, [1,5] SiÀH addition to the NC triple bond remains a great synthetic challenge.…”
mentioning
confidence: 99%
“…4) The role of the substituent on the oxazoline rings in 6, 8, and 9 can be attributed to the shielding of one of the faces of the catalyst by the Ph group. [15] Accordingly, the following mechanistic picture can be drawn: the N,N-chelation of Cl 3 SiH by the catalyst creates an activated hydrosilylating species, while another molecule of Cl 3 SiH is likely to activate the ketone by coordination to the oxygen atom in the E fashion. [16] The ketone-Cl 3 SiH complex will then approach the catalyst-Cl 3 SiH complex from the lesshindered side (as dictated by the remote chiral center in the catalyst).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the current methods usually perform well with either ketones or imines, but rarely with both classes. [4] The alternative metal-free methods [2,5] are rare and considerably less effective; [6] nevertheless, a promising development has recently been reported, [7] which relies on Cl 3 SiH, an inexpensive and easy-to-handle reducing agent. [8] Herein, we report an organocatalytic hydrosilylation applicable to both ketones and ketimines.…”
mentioning
confidence: 99%